Fitoplancton de una laguna pampásica (San Miguel del Monte, Buenos Aires, Argentina): variación espacio-temporal de los grupos funcionales - Quaíni, Karina Paola (2008)
Phytoplankton assemblages were analyzed taking into account the functional groups in a shallow lake connected to the lower basin of Salado River. Samples were obtained monthly (9/1997-8/1998), from the affluent (E1), San Miguel del Monte lake (E2) and the connection with Las Perdices lake (E3). Species with biovolume higher than 0.5 mm 3 .l-1 and contributing to 5-73 % of total biovolume were selected. Moderate eutrophy favored the development of filamentous cyanobacteria (S1 and S2 functional groups), unicellular flagellates (Y and X2) and nitrogen fixed cyanobacteria (H and H1). Colonial cyanobacteria (X1 and K) coexisted with filamentous cyanobacteria in coincidence with high phosphorus values. Biovolume of unicellular flagellates increased in relation to the input of nutrients from Salado River. At E3, filamentous cyanobacteria (S1, S2, H1 and H) were dominant and species of Y and X1 groups were co-dominant. At E1, colonial cyanobacteria (M), typical from eutrophic lakes with high organic matter, were found in high densities. Phytoplankton functional classification introduced by Reynolds gives an invaluable information and represents a good complement to understand the ecological characteristics of the algae and the phytoplankton dynamics in San Miguel del Monte Lake».